NASKAH PUBLIKASI FAKTOR- FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI UNTUK BERKARIER SEBAGAI AKUNTAN PUBLIK (Studi Kasus pada Mahasiswa Semester 6 ke Atas Universitas Stikubank Semarang) - Dwi Hastuti, 13.05.52.0109; Kartika, Andi (Students' Journal of Accounting and Banking, 2018)
The purpose of this study is Student accounting after graduation can choose the type of career in accordance with the field of science one of them is as a public accountant. This study aims to analyze the factors that affect the interests of accounting students for a career as a public accountant. Samples used in this study are students accounting semester 6 and above University Stikubank (UNISBANK) Semarang with the number of respondents as many as 88 people. The data used in this study is primary data that the data obtained from the distribution of questionnaires to students majoring in accounting. Based on the results of research and analysis that have been done can be concluded: Variable financial reward, professional recognition, social values, work environment, and personality have a significant positive effect on the interest of accounting students career as a public accountant. While the variables of professional training and job market considerations have a significant negative effect on the interest of accounting career students as public accountants. The financial reward variable is a variable that has a considerable effect on the interest of accounting students as a puclic accountant.Keywords   Financial awards, professional training, professional recognition, social values, work environment, job market considerations, and personality towards the interests of accounting students career as public accountants